You take your past with you wherever you go : the experiences and results of mature adult student graduates engagement with third level education at Trinity College Dublin - Giblin, Michele (Trinity College (Dublin, Ireland). School of Education, 2015)
The concept of lifelong learning has evolved over a number of decades and has been channelled through various supranational and national organisations, for instance UNESCO (1960), OECD (1973), EU(1996), HEA (2010) and expressed in many policy documents, papers recommendations and research studies (Delors report, UNESCO, 1996; OECD 96/102, report; Lisbon strategy, 2000; Irish Modernisation agenda, 2011; National Strategy for Higher Education to 2030, Hunt report, 2011; Fleming, Loxley, Kenny & Finnegan 2009).
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin